Iraq : Technical Assistance Report-Guarantees and Extra Budgetary Funds Management. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2021)
Iraq is substantially exposed to fiscal risks related to guarantees issued by the State, with a stock of guarantees related to foreign currency service payments and debt of USD 21.7 billion at end-June 2017 and a stock of domestic guarantees that remains to be fully assessed. In 2017, the Council of Ministers approved a set of procedures to tighten controls on the approval of State guarantees. Nevertheless, misreporting cases highlight the need to further strengthen capacities and institutional arrangements to effectively identify and monitor the fiscal implications of guarantees, including in the context of EBFs' operations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Iraq